Combinatorial Screening of Pancreatic Adenocarcinoma Reveals Sensitivity to Drug Combinations Including Bromodomain Inhibitor plus Neddylation Inhibitor - Langdon, Casey G. (Mol Cancer Ther, 2017)
Pancreatic adenocarcinoma (PDAC) is the fourth most common cause of cancer death in the United States. PDAC is difficult to manage effectively, with a five-year survival rate of only 5%. PDAC is largely driven by activating KRAS mutations, and as such, cannot be directly targeted with therapeutic agents that affect the activated protein. Instead, inhibition of downstream signaling and other targets will be necessary to effectively manage PDAC. Here, we describe a tiered single-agent and combination compound screen to identify targeted agents that impair growth of a panel of PDAC cell lines. Several of the combinations identified from the screen were further validated for efficacy and mechanism. Combination of the bromodomain inhibitor JQ1 and the neddylation inhibitor MLN4294 altered production of reactive oxygen species in PDAC cells, ultimately leading to defects in the DNA damage response. Dual bromodomain/neddylation blockade inhibited in vivo growth of PDAC cell line xenografts. Overall, this work revealed novel combinatorial regimens, including JQ1 plus MLN4294, which show promise for the treatment of RAS-driven PDAC.